Administrative governance and its role in enhancing competitiveness from the point of view of employees at Damascus University (Damascus University Journal of educational and Psychologyical sciences, 2024)
The research aims to identify the degree of availability of administrative governance and the degree of availability of competitiveness at the University of Damascus, and to know the impact of administrative governance in enhancing the competitiveness of the university. The researcher used the descriptive analytical method and the questionnaire as a research tool, which was applied to a sample of (80) administrative employees at the University of Damascus drawn in a method A simple random sample from the original population consisting of (1446) administrative employees. The most important findings of the research are that the degree of availability of administrative governance at the university is low while the degree of competitiveness was moderate, in addition to the absence of statistically significant differences between the averages of the answers of the sample members according to the variable Academic qualification, while there are statistically significant differences between the averages of the sample members’ answers according to the job title variable and in favor of the administrative director.
Keywords: administrative governance; competitiveness